Fatigue failure behavior of aramid fiber reinforced styrene butadiene rubber composite with different fiber coatings. Issue 6 (23rd March 2022) - Zhang, Hao; Yin, Lianpeng; Luo, Zhu; Zhong, Jincheng; Wang, Xingyu; Xiang, Kun
Abstract: This study investigates the true stress evolution of aramid fiber (AF) reinforced styrene butadiene rubber (SBR)/carbon black (CB) composites with different interface characteristics in the fatigue failure process. AF was coated with epoxy‐functionalized silane ( γ ‐propyltrimethoxysilane, KH560) and butadiene styrene vinyl‐pyridine rubber latex (VPL). The influence of the interface characteristics on the mechanical and fatigue properties of the composites were explored. The results show that the fatigue crack growth rate of the rubber composites reinforced by a coated fiber with a flexible interface layer was significantly reduced. Furthermore, the fatigue failure behavior of the notched samples can be characterized by true stress evolution. The power‐law relationship of the true stress with both fatigue cycle and crack growth length was founded. Meanwhile, the stress evolution mechanism in the process of fatigue failure was discussed and the critical crack length corresponding to the point where the true stress begins to accelerate is found. Highlights: The fatigue crack growth rate of the rubber composites reinforced by a coated fiber with a flexible interface layer was significantly reduced. The fatigue failure behavior of the notched samples within the strain‐controlled fatigue process can be characterized by true stress evolution, and the fatigue life of the notched samples is expected to be predicted by the true stress variation in the subsequent research. The power‐law relationship of the true stress with both fatigue cycle and crack growth length was founded. The stress evolution mechanism within fatigue failure processes was discussed.